HUBUNGAN ANTARA MOTIVASI BERKOMPETISI DENGAN PROKRASTINASI AKADEMIK PADA SISWA SMA NEGERI 1 SALATIGA - Ferry Afriyan Komara; Imam Setyawan (Faculty of Psychology, Diponegoro University, 2014)
Credit Semester System give opportunity for students to finish their study faster than usual. For finish all of task greatly, the students should manage times really good to do not academic procrastination. Which one factor that influence academic procrastination is motivation. The purpose of this research is to know the relation between competing motivation with academic procrastination in students of 1 Senior High School Salatiga City which had using Credit Semester System, and how much competing motivation give effective contribution to academic procrastination. Population research is students of 1 Senior High School Salatiga who had use Credit Semester System as long as their study, numbered 451 in 17 classroom. The sampling technique is done by cluster random sampling. Collecting data on this research is using academic procrastination scale (29 item α = 0,917) and competing motivation (29 item α = 0,889). Data analysis performed by simple regression analysis, Based on analysis of data obtained is the correlation coefficient value (rxy) -0,657 with p = (p